2000
DOI: 10.1103/physreva.62.053606
|View full text |Cite
|
Sign up to set email alerts
|

Dark-soliton states of Bose-Einstein condensates in anisotropic traps

Abstract: Dark soliton states of Bose-Einstein condensates in harmonic traps are studied both analytically and computationally by the direct solution of the Gross-Pitaevskii equation in three dimensions. The ground and self-consistent excited states are found numerically by relaxation in imaginary time. The energy of a stationary soliton in a harmonic trap is shown to be independent of density and geometry for large numbers of atoms. Large amplitude field modulation at a frequency resonant with the energy of a dark soli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
206
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(217 citation statements)
references
References 46 publications
(75 reference statements)
10
206
0
1
Order By: Relevance
“…Using α = 1.6 and γ = 0.02, our simulations show that L x blows up after 15 ms of excitation. At this point, the condensate forms wavy patterns which develop to dark solitary waves which subsequently decay into several vortex pairs via the snake instability [29]. A more complex dynamics takes place after the first events of vortex formation, consisting in the generation of an undetermined number of vortices which characterizes the emergence of the turbulent regime.…”
Section: Numerical Calculations Formentioning
confidence: 99%
“…Using α = 1.6 and γ = 0.02, our simulations show that L x blows up after 15 ms of excitation. At this point, the condensate forms wavy patterns which develop to dark solitary waves which subsequently decay into several vortex pairs via the snake instability [29]. A more complex dynamics takes place after the first events of vortex formation, consisting in the generation of an undetermined number of vortices which characterizes the emergence of the turbulent regime.…”
Section: Numerical Calculations Formentioning
confidence: 99%
“…In particular, it has been found that in elongated harmonic traps a DS oscillates with frequency Ω/ √ 2, where Ω is the axial trap frequency. Thermal [11] and dynamical [12] instabilities, mainly referring to rectilinear DSs, have been investigated. On the other hand, generalizations of the rectilinear solitons, such as ring-shaped DSs, have recently been proposed [13].…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of dark solitons (DSs) in the presence of the external magnetic trap has been extensively studied [4], including thermal [5] and dynamical [6] instabilities. More recently, apart from the rectilinear DSs, ring-shaped counterparts were predicted in BECs [7].…”
mentioning
confidence: 99%